[Radiation cytogenetics of multilocus deletions and the principles of the superchromomeric organization of eukaryotic euchromatin.] - Alexandrova, M.V.; Lapidus, I.L.; Aleksandrov, I.D.; Filimonov, A.S. (Radiatsionnaia biologiia, radioecologiia, 1996)
Fine cytological analysis of 72 gamma ray- and neutron-induced multilocus deletions (MLD) at the b, cn and vg regions of Drosophila melanogaster polytene chromosomes combined with the complementation assay at the b region is used to detect precisely the size and location of the MLD ends relatively to chromomeres and to each other. The basic principles of the MLD induction are found to be the same for three studied genome regions, showing that the folding of the interphase chromatin at the superchromomeric level is non-random and follows the megasolenoid-rosette model which is presented and discussed.